Types and cost of retaining walls systems constructed in Johor - Sow, Kian Cha, 1987-; Yahya Mohamad Yatim, supervisor; Fakulti Alam Bina (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2010)
Project Paper (Sarjana Muda Ukur Bahan) - Universiti Teknologi Malaysia, 2010